What horizon for price stability - Frank Smets (European Central Bank (ECB), 2000)
This paper analyses in a unified framework the twin issues of the appropriate horizon for achieving price stability in the face of unexpected disturbances and the choice of a price level versus an inflation objective. Using a small estimated forward-looking model of the euro area economy, the three main findings are: 1) The policy horizon becomes shorter the greater the weight on price stability in society's objective function, the higher the degree of 'forward-lookingness' in the economy and the greater the slope of the Phillips curve; 2) The optimal policy horizon for a price level objective is generally greater than that for an inflation objective; 3) Even if society cares about inflation stabilisation (rather than the stabilisation of the price level), it often pays to give the central bank a price level objective (rather than an inflation objective), provided the horizon is optimally chosen to be somewhat longer and there is a small weight on interest rate stabilisation in the loss function. This result depends, however, on the structure of the economy.
Keywords: E4; E5; 330; euro area; monetary policy; policy rules; strategy